Collaborative Strategic Reading (CSR) and Reading Comprehension across Reading Motivation - Siti Nur Jannah (Graduate Program, University of Islam Malang, 2020)
This research conducted to probe the outcome of CSR on reading comprehension across reading motivation. Moreover, this research aims to investigate the modification concerning the students taught with CSR and the students taught with conventional strategy on reading comprehension. Nonetheless, the variance between the students with intrinsic reading motivation and extrinsic reading motivation on reading comprehension, and the interaction within CSR and students reading motivation on reading comprehension. This research used quasi-experimental research. Furthermore, the sample of this research was two classes of seventh grade students of SMP Negeri 12 Malang. However, the instrument that used in this research was posttest and questionnaire, and examined by SPSS Version 20. The result revealed that the students taught by using CSR have higher score than the conventional strategy. CSR was effective students’ reading comprehension. The outcomes point out that students’ reading motivation does not affect to CSR on reading comprehension. In contrast, it has no interaction between CSR and the reading motivation.